Pauximyia, a new genus of Odiniidae (Diptera: Acalyptratae) with description of two new species from Brazil - Limeira-De-Oliveira, Francisco; Marques, Dayse Willkenia A.; Gaimari, Stephen D.; Rafael, José A. (Zootaxa, 2020)
A new genus of odiniids (Odiniidae: Traginopinae) is described from Brazil, Pauximyia gen. nov., with two species, P. oliveirai sp. nov. (type species) and P. vidali sp. nov. A modified key to the Neotropical genera of the family and for the two Pauximyia gen. nov. species is provided.